Effects of fibrinogen and fibrin on the migration of vascular smooth muscle cells in vitro - Naito, Michitaka; Hayashi, Toshio; Kuzuya, Masafumi; Funaki, Chiaki; Asai, Kanichi; Kuzuya, Fumio (Atherosclerosis, 1990)
The migration of vascular smooth muscle cells from the media into the intima and their proliferation in the intima play an important role in the pathogenesis of atherosclerosis. We examined the effects of fibrinogen and fibrin on the migration of cultured bovine aortic smooth muscle cells using a modified Boyden chamber assay. The cells migrated to a gradient of soluble fibrinogen. Checkerboard analysis indicated that the effect was largely directional in nature (chemotaxis). The cells also migrated in a dose-dependent manner to a gradient of substrate-bound fibrinogen (haptotaxis). Fibrin, converted from substrate-bound fibrinogen by thrombin, also induced haptotaxis of smooth muscle cells. These observations suggest that, by recruiting smooth muscle cells from the media into the intima, fibrinogen and fibrin may be involved in the pathogenesis of arterial intimal thickening, atherosclerosis, and the organization of a thrombus.